(untitled) (Swiss Medical Weekly, 2024)
AIM OF THE STUDY: Oral immunotherapy (OIT) is increasingly used for the treatment of childhood food allergies, with limited data available on cashew nut OIT. This real-life study investigated the safety and feasibility of cashew nut OIT, comparing it with peanut OIT, with a focus on the up-dosing process. METHODS: We analysed cashew nut (n = 24) and peanut (n = 38) OIT cases with treatment initiated between 2018 and 2022 at the University Childrenʼs Hospital Basel. All patients who commenced therapy within this time frame were enrolled without prior selection. Two different starting protocols were used. Within the up-dosing protocol, the nut intake was incrementally increased by 20–30% every 2 weeks until reaching a maintenance dose of 1 g of nut protein. After consuming the maintenance dose regularly for 18–24 months, a second oral food challenge was performed. Patients who passed this challenge were considered desensitised. The safety of the therapy was evaluated based on the severity of adverse reactions during the up-dosing phase. Symptom severity was evaluated using the validated ordinal food allergy severity scale (o-FASS-5). RESULTS: Over the study period, 33% of cashew nut-allergic and 63% of peanut-allergic patients experienced mild to moderate allergic reactions. Severe allergic reactions occurred in five peanut-allergic children with high baseline allergen-specific IgE levels. Six patients with peanut, and none with cashew nut OIT, discontinued the therapy due to adverse reactions. The mean duration to reach the maintenance phase was longer for children with asthma or another food allergy. Among children who already underwent the second oral food challenge, desensitisation was achieved in 91% (11 out of 12) of cashew nut- and 73% (11 out of 15) of peanut-allergic patients. CONCLUSION: Cashew nut OIT had a low severity of adverse reactions and was generally well-tolerated. However, patient characteristics influenced side effect risk and treatment duration, emphasising the need for individualised OIT strategies.